Hepatoprotective effect of leaves of aqueous ethanol extract of Cestrum nocturnum against paracetamol-induced hepatotoxicity - M. Imran Qadir; Muhammad Sajid Al Murad; Muhammad Ali; Mohammad Saleem; Ammad Ahmad Farooqi (Bangladesh Pharmacological Society, 2014)
The hepatoprotective activities of Cestrum nocturnum (Queen of Night) was evaluated against the paracetamol induced hepatotoxicity in the mice. Aqueous ethanol (30:70) extract of plant was obtained by maceration. Results showed that aqueous ethanol extract of C. nocturnum (250 mg/kg and 500 mg/kg) produced significant (p<0.05) hepatoprotective activities against paracetamol induced liver injury in Swiss albino mice. Histopathalogical studied of liver further supported the hepatoprotective effects of C. notrunum. Phytochemical screening showed the presence of alkaloids, flavonoids, saponins, terpenes, phenolic compounds, carbohydrates and volatile oils. Most of the flavonoids have hepatoprotective activity. Therefore, the hepatoprotective activity of C. nocturnum may be due to the presence of flavonoids and phenolic components. It was concluded from the present study that aqueous ethanol extract of leaves of C. nocturnum has hepatoprotective activity against the paracetamol-induced hepatotoxicity in albino mice.